KUALITAS MOTILITAS DAN VIABILITAS SPERMATOZOA DARI SEMEN AFKIR SAPI LIMOUSIN PADA PENGENCER SUSU SKIM KUNING TELUR SITRAT DENGAN PENAMBAHAN BERBAGAI KADAR GLUKOSA - Irvanto, Rudi; Hardijanto, Hardijanto; Paramita, Widya; Susilowati, Suherni; Damayanti L, Tita; Safitri, Erma (Universitas Airlangga, 2018)
Quality of spermatozoa motility and viability from rejected limousin bull semen diluted with skim milk egg yolk sitrat added with various levels of glucose. Glucose level used were 0%, 0,5%, 1,5%, 2,5%, and 3,5%. Writer was using on four years old Limousine bull. Bull semen used in this research was bull rejected semen with bellow 70% motility. Semen observation was done at 0 hour, 24 hours and 48 hours. Research design used in this study was completely randomized design with faktorial pattern with 5 replicates. Highest result in motility this research was showed at 24 hours with 30% value in glucose 2,5% treatment and 48 hours with 10% value. The lowest result showed in glucose 0% treatment at 24 hours and 0% at 48 hours. Highest result in viability showed on glucose 2,5% treatment with 62,6% value at 24 hours and at 48 hours with 53,4% value. Lowest result in viability showed on glucose 0% treatment with 44,2% value at 24 hours and 31,4% value at 48 hours.